Enrichment of cancer stem cell subpopulation alters the glycogene expression profile of colorectal cancer cells - Jéssica de Andrade-da-Costa; Michelle de-Souza-Ferreira; Nathália Campos dos Santos Touça; Annie Cristhine Moraes Sousa-Squiavinato; Sheila Coelho Soares-Lima; José Andrés Morgado-Díaz; Julio Cesar Madureira de-Freitas-Junior (Discover Oncology, 2024)
Abstract Colorectal cancer (CRC) has a high mortality rate, resulting from the processes of metastasis and disease recurrence. Cancer stem cells (CSCs) are believed to be crucial for both processes, as they ensure the maintenance of the tumor bulk, in addition to being intrinsically resistant to conventional therapies. Thus, the present study aimed to investigate glycobiomarkers in colorectal cancer stem cell subpopulations. For this purpose, a sphere formation assay was standardized for CACO-2 and HT-29 cell lines, which were monitored through gene expression analysis of five known CSC markers (CD24, CD44, ALDH1, LGR5, and PROM1). Compared to the parental condition (2D), a reduction in CD24 expression was seen in CACO-2, while in HT-29 an increase in the expression levels of ALDH1, LGR5, and PROM1 was observed. Regarding glycogenes, eight of them (ST3GAL1, OGT, OGA, MGAT5, GFAT1, GFAT2, B4GALT1 e B3GNT2) have had their expression monitored. An increase in B3GNT2, OGT, and OGA was observed in the HT-29 sphere condition. On the other hand, no change in the glycogenes expression was observed in CACO-2. In silico correlation analyses (CSCs markers versus glycogenes) using TCGA data from colon and rectum carcinoma samples showed a weak positive correlation between LGR5 vs OGA expression regardless of the sample location. In addition, an increase in the expression of LGR5, OGA, and OGT as well as a decrease in the expression of ALDH1 were observed in colon carcinoma samples when compared to the adjacent normal tissue. Interestingly, greater OGA expression resulted in both lower overall survival of colon carcinoma patients and lower disease-free survival of rectum carcinoma patients. Therefore, our data indicates that OGA expression correlates with CSC markers and directly impacts the survival of colorectal carcinoma patients.